Dynamic reputation–based consensus mechanism: Real-time transactions for energy blockchain - Wenjun Cai; Wei Jiang; Ke Xie; Yan Zhu; Yingli Liu; Tao Shen (International Journal of Distributed Sensor Networks)
The energy blockchain is a distributed Internet protocol for energy transactions between nodes in power systems. The consensus algorithm is the core component of the energy blockchain and has an essential impact on its application. At present, in the implementation of the energy blockchain, there are problems such as low transaction throughput (transactions per second) and high latency, which cannot meet the application requirements of real-time processing transactions in the energy field. To this end, according to the analysis of conventional blockchain consensus algorithm and traditional practical Byzantine fault tolerance algorithm, a dynamic-reputation practical Byzantine fault tolerance algorithm for the energy blockchain is proposed. The dynamic-reputation practical Byzantine fault tolerance algorithm adopts a credit-based consortium node consensus election method. The monitoring node divides the remaining nodes into two types of nodes according to the reputation value: the consensus node and the secondary node, which, respectively, participate in different stages of the block generation process, and dynamically update the consensus nodes with low reputation ratings. By constructing the experimental platform simulation, the test results verify the effectiveness of the dynamic-reputation practical Byzantine fault tolerance algorithm. Compared with the algorithm of the fabric platform, the dynamic-reputation practical Byzantine fault tolerance algorithm improves the transaction processing speed and is suitable for the blockchain application in the energy field.